Determinants of Indigenous Organic Farming Practices Adoption among Cassava Farmers in Kwara State, Nigeria - Abdulgafar, Habeebullahi; Isah, Aliyu; Ado, Garba (FUDMA Journal of Sciences, 2026)
This study examined the determinants of indigenous organic farming practices adoption among cassava farmers in Kwara State, Nigeria. Multistage sampling procedure was used to select 90 cassava farmers from Kwara State Agricultural Development Programme (KWADP) Zone C. Data were collected using structured questionnaires and analyzed using descriptive statistics and binary logistic regression. The results showed that 64.4% of the respondents were male, while 63.3% were within the economically active age range of 20–40 years. About 70.0% of the farmers had tertiary education, and 57.8% had household sizes of between 4–6 persons. Institutional characteristics revealed that 68.9% of the respondents were members of farmers’ associations, and majority of them 83.3% had access to extension services, most of them 71.1% had access to credit for farming activities. The logistic regression results indicated that education level (β = 0.683, p < 0.05), farming experience (β = 0.686, p < 0.05), access to extension services (β = 2.739, p < 0.01), access to credit (β = 2.645, p < 0.05), and membership of farmers’ associations (β = 1.231, p < 0.05) significantly influenced adoption of indigenous organic farming practices. Access to extension services increased the likelihood of adoption by over fifteen times. The study concludes that institutional support and farmers’ capacity-building are critical to enhancing indigenous organic farming adoption among cassava farmers. Strengthening extension delivery, improving credit access, and promoting farmers’ organizations are recommended to scale up sustainable cassava production in the study area.